(untitled) (Scientific journal of the Fergana State University, 2023)
The Government of Uzbekistan pays great attention to handicrafts, the preservation and development of its traditions. Determining the place of handicraft in the modern society of the republic and finding out the forecasts for its development is one of the objectives of this article. Researchers of this problem find it difficult to overcome the gap between the amount of knowledge provided to society by information and communication technologies and the seeming unpreparedness of the modern Uzbek artisan to accept and apply these technologies. Our observations show that the artisans of the Fergana Valley possess the full scope of knowledge they need in production. Applying the latest technologies in the craft, they preserve the most ancient traditions.